Friction Modeling and Control in Boundary Lubrication - Dupont, Pierre E.; Dunlap, Eric P. (American Control Conference, 1993, 1993)
It has been known for many years that stick-slip can often be eliminated from a system by stiffening it. More recently, it has been shown that for a negatively-sloped friction-velocity curve, a frictional lag must be present for machine stiffness to produce this stabilizing effect [2,10]. In this paper, experiments involving dry and lubricated line contacts of hardened tool steel are described and a state variable friction model possessing this lag is fit to the data. The model and associated parameter values provide a means for computing lower bounds on the PD gains necessary for steady motion in the boundary lubrication regime.